Physicochemical evaluation and spectroscopic characterisation of gelatine from shank and toes of Gallus gallus domesticus - Abdullah, M.S.P.; Noordin, M.I.; Ismail, S.I.M.; Nyamathulla, S.; Jasamai, M.; Wai, L.K.; Mustapha, N.M.; Shamsuddin, A.F. (Penerbit Universiti Kebangsaan Malaysia, 2016)
Growing needs, inadequate supply along with health and religious issues are reasons for the increase in the demand for an alternative source of gelatine in the food and pharmaceutical industries. This study was conducted to optimize the process for producing halal-compliant gelatine from chicken waste; chicken shank and toes (CST). Double extraction process employed produced gelatine which was vitreous, lightweight and gossamer in appearance. Gelatine yield was 9.52%(w/w) with a pH of 3.85, moisture content of 7.17%, total protein content of 93.77%, total fat content of 0.93% and total ash of 1.57%. The Bloom strength of the CST gelatine (148.33 ± 5.51) was found to be slightly lower than the commercially available bovine gelatine (BS) (169.33 ± 58.53) (P > 0.05). Amino acid analysis showed that the CST gelatine (91.38 ± 1.01%) was comparable to BS gelatine (90.65 ± 1.56%)(P > 0.05). Double extraction has been shown to successfully increase the surface area to volume ratio of CST waste resulting in increased yield in gelatine and protein with lower total fat content obtained. The test results obtained showed that the CST gelatine produced through this method complies with pharmaceutical standards.